Obesity-Associated Myeloid-Derived Suppressor Cells Promote Apoptosis of Tumor-Infiltrating CD8 T Cells and Immunotherapy Resistance in Breast Cancer - Gibson, Justin T.; Orlandella, Rachael M.; Turbitt, William J.; Behring, Michael; Manne, Upender; Sorge, Robert E.; Norian, Lyse A. (Frontiers in Immunology, 2020)
Nearly 70% of adults in the US are currently overweight or obese. Despite such high prevalence, the impact of obesity on anti-tumor immunity and immunotherapy outcomes remains incompletely understood, particularly in patients with breast cancer. Here, we addressed these gaps in knowledge using two murine models of breast cancer combined with diet-induced obesity. We report that obesity increases CXCL1 concentrations in the mammary tumor microenvironment, driving CXCR2-mediated chemotaxis and accumulation of granulocytic myeloid-derived suppressor cells (G-MDSCs) expressing Fas ligand (FasL). Obesity simultaneously promotes hyperactivation of CD8 tumor-infiltrating lymphocytes (TILs), as evidenced by increased expression of CD44, PD-1, Ki-67, IFN, and the death receptor Fas. Accordingly, G-MDSCs induce Fas/FasL-mediated apoptosis of CD8 T cells ex vivo and in vivo. These changes promote immunotherapy resistance in obese mice. Disruption of CXCR2-mediated G-MDSC chemotaxis in obese mice is sufficient to limit intratumoral G-MDSC accumulation and improve immunotherapy outcomes. The translational relevance of our findings is demonstrated by transcriptomic analyses of human breast tumor tissues, which reveal positive associations between CXCL1 expression and body mass index, poor survival, and a MDSC gene signature. Further, this MDSC gene signature is positively associated with FASLG expression. Thus, we have identified a pathway wherein obesity leads to increased intratumoral CXCL1 concentrations, which promotes CXCR2-mediated accumulation of FasL+ G-MDSCs, resulting in heightened CD8 TIL apoptosis and immunotherapy resistance. Disruption of this pathway may improve immunotherapy outcomes in patients with breast cancer and obesity.